Is percutaneous drainage better than endoscopic drainage in the management of patients with malignant obstructive jaundice? A meta-analysis of RCTs - Bian, Cnogwen; Fang, Yuan; Xia, Jun; Shi, Lan; Huang, Hanfei; Xiong, Qiru; Wu, Ruolin; Zeng, Zhong (Frontiers in Oncology, 2023)
To compare the safety and efficacy of endoscopic retrograde cholangiopancreatography (ERCP) and percutaneous transhepatic cholangial drainage (PTCD) in the treatment of malignant obstructive jaundice, a systematic review and meta-analysis of published studies was undertaken to assess the differences between the two procedures in terms of efficacy and safety. From November 2000 to November 2022, the Embase, PubMed, MEDLINE, and Cochrane databases were searched for randomized controlled trials (RCTs) on the treatment of malignant obstructive jaundice with ERCP or PTCD. Two investigators independently assessed the quality of the included studies and extracted the data. Six RCTs, including 407 patients, were included. The results of the meta-analysis showed that the overall technical success rate in the ERCP group was significantly lower than that in the PTCD group (Z=3.19, P=0.001, OR=0.31 (95% CI: 0.15-0.64)), but with a higher overall procedure-related complication incidence rate (Z=2.57, P=0.01, OR=0.55 (95% CI: 0.34-0.87)). The incidence of procedure-related pancreatitis in the ERCP group was higher than that in the PTCD group (Z=2.80, P=0.005, OR=5.29 (95% CI: 1.65-16.97)), and the differences were statistically significant. No significant difference was observed between the two groups when the clinical efficacy, postoperative cholangitis, and bleeding rate were compared.Both treatments for malignant obstructive jaundice were efficacious and safe. However, the PTCD group had a greater technique success rate and a lower incidence of postoperative pancreatitis.The present meta-analysis has been registered in PROSPERO